2018
DOI: 10.1021/acs.chemrev.8b00322
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lipid Nanodomains

Abstract: Lipid membranes can spontaneously organize their components into domains of different sizes and properties. The organization of membrane lipids into nanodomains might potentially play a role in vital functions of cells and organisms. Model membranes represent attractive systems to study lipid nanodomains, which cannot be directly addressed in living cells with the currently available methods. This review summarizes the knowledge on lipid nanodomains in model membranes and exposes how their specific character c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
204
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(206 citation statements)
references
References 395 publications
2
204
0
Order By: Relevance
“…Because of the large head group, it has a low percolation threshold (calculated to be ~22 mol%; that is, at mol% ≥ 22, GM 1 forms a network essentially blanketing the membrane leaflet). At lower (physiological) mol%, GM 1 forms clusters and ordered microphases of various types, such as rafts (liquid‐ordered phase ≥1 mol% of GM 1 ) and nanoclusters (less ordered and more dynamic than rafts) in combination with SM and cholesterol . Using ultrastructural methods, and later, using radiolabeled and biotin‐labeled GM 1 , it was shown that this ganglioside (and perhaps others) also accumulates in caveolae and in endosomes of certain cancer cell lines …”
Section: The Role Of Gangliosides In Combination With Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the large head group, it has a low percolation threshold (calculated to be ~22 mol%; that is, at mol% ≥ 22, GM 1 forms a network essentially blanketing the membrane leaflet). At lower (physiological) mol%, GM 1 forms clusters and ordered microphases of various types, such as rafts (liquid‐ordered phase ≥1 mol% of GM 1 ) and nanoclusters (less ordered and more dynamic than rafts) in combination with SM and cholesterol . Using ultrastructural methods, and later, using radiolabeled and biotin‐labeled GM 1 , it was shown that this ganglioside (and perhaps others) also accumulates in caveolae and in endosomes of certain cancer cell lines …”
Section: The Role Of Gangliosides In Combination With Cholesterolmentioning
confidence: 99%
“…At lower (physiological) mol%, GM 1 forms clusters and ordered microphases of various types, such as rafts (liquidordered phase ≥1 mol% of GM 1 ) and nanoclusters (less ordered and more dynamic than rafts) in combination with SM and cholesterol. 86,87 Using ultrastructural methods, and later, using radiolabeled and biotin-labeled GM 1 , it was shown that this ganglioside (and perhaps others) also accumulates in caveolae and in endosomes of certain cancer cell lines. 88,89 The anionic nature of gangliosides depends in part on the number of sialic acid residues in a particular subclass of these lipids.…”
Section: The Role Of Gangliosides In Combination With Cholesterolmentioning
confidence: 99%
“…It is difficult to discriminate between D-DPPC and L-DPPC bilayers by the observation of normal physicochemical properties, but circular dichroism (CD) spectra constitutes an excellent method to characterize the chiral properties of constituents. A helical molecule, ie, 2-hydroxymethyl [5]thiaheterohelicene (5HM), was reported as a CD probe to examine the chiral membrane environments. 68 Strong CD absorptions of 5HM in D-or L-DPPC bilayers readily permitted the discrimination of the chiral lipid environments based on the opposite signs of the Cotton effects.…”
Section: Glycerophospholipids and Their Enantiomersmentioning
confidence: 99%
“…The assembly of chiral lipids serves as a platform for functional biological membranes, which can regulate the functions and enzymatic reactions of membrane receptors that occur on the chiral membrane surface and in membrane leaflets. Interlipid interactions in membranes occur in a stereoselective manner and induce the formation of the lipid phase and domains with various sizes ranging from tens of micrometers to single‐digit nanometers in model membranes. Some membrane proteins are known to specifically interact with chiral ligand lipids, and concurrent interactions with the surrounding lipids lead to the regulation of functions and localization of proteins .…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1002/advs.201901935 lipid transport, lipid microdomain formation, or the interaction of lipids with membrane proteins. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] An important prerequisite for such studies is a mode of intracellular delivery that does not impair the physiological integrity of the cell membrane. Fusogenic liposomes have been introduced to integrate amphiphilic lipids into the plasma membrane; however, the presence of fusogenic lipids in these systems can affect membrane properties.…”
mentioning
confidence: 99%